Cytogenetics of the skinks (Reptilia, Scincidae) from Thailand; III: the first karyological study of Sphenomorphus maculatus and Jarujinia bipedalis - Prasopsin S. (2017)
© 2017 Dipartimento di Biologia Evoluzionistica, Università di Firenze. This is a karyological study of male and female Sphenomorphus maculatus from Khon Kaen Province in Northeastern Thailand, and female Jarujinia bipedalis from Kanchanaburi Province in Central Thailand. Chromosomes of two species were prepared by the squash technique from the bone marrow and testis. Conventional staining and Ag-NOR banding techniques were applied to stain the chromosome with Giemsa’s solution and silver nitrate solution, respectively. The results showed that the diploid chromosome number of Sphenomorphus maculatus and Jarujinia bipedalis was 30 and the fundamental number (NF) was 44. There were eight large metacentric, two medium metacentric, four small metacentric and 16 microchromosomes in Sphenomorphus maculatus and eight large metacentric, six small metacentric, two small telocentric and 14 microchromosomes in Jarujinia bipedalis. There was no irregularly sized chromosome related to sex in either species. For Sphenomorphus maculatus, NORs are located at the telomere on the long arms of the second pair of the metacentric chromosome. The karyotype formulae were deduced as: 2n (30) = L m 8  + M m 2  + S m 4  + 16 microchromosomes and 2n (30) = L m 8  + S m 6  + S t 2  + 14 microchromosomes for Sphenomorphus maculatus and Jarujinia bipedalis, respectively.